Effects of holy basil (Ocimum sanctum) on viral disease of chili (Capsicum annum L.) under mixed crop cultivation - Arsi, Arsi; SHK, Suparman; Lailaturrahmi; Hamidson, Harman; Pujiastuti, Yulia; Umayah, Abu; Gunawan, Bambang; Pratama, Rahmat; Irsan, Chandra; Suwandi (Universitas Lampung, 2023)
Chili is one of the important commodities in Indonesia. Chili cultivation faces many obstacles, leading to a decrease in production, such as virus infections. Yellow leaf curl and curly top viruses are groups of viruses that are often found in chili fields. This research was conducted to investigate the effect of intercropping (basil-chili) in suppressing viral diseases, especially yellow leaf curl and curly top viruses. A Randomized block design was used for this research, including intercropping and monoculture. The parameters observed in this study included disease incidence and intensity, the number and weight of chilies. Symptoms of virus infection include leaf curl, yellowing, and stunting. The disease has been reported to be transmitted by insect vectors, such as Aphis gossypii and Bemisia tabaci. The results showed that the incidence and intensity of yellow leaf curl and curly top virus diseases in chili pepper and basil plants were not significantly different in each treatment. The number of healthy chilies and their weight were also not significantly different. Damaged chilies are fruits that have been attacked by fruit flies. Basil intercropped with chilies attracts fruit flies, which affects the quantity and weight of the harvested chilies. The population of B. tabaci was significantly different in each treatment, while A. gossypii did not show significant differences among the treatments. Intercropping basil and chili increased the population of A. gossypii, while the population of B. tabaci decreased in this treatment. These two insect pests are vectors for yellow leaf curl and curly top viruses.